The Effects of Different LED Lights on the Main Nutritional Compositions of Isochrysis zhanjiangensis - Yanbin Sun; Jiaxing Zhang; Jilin Xu; Jiayi Cao; Yanrong Li (Fishes, 2023)
Light irradiation plays an important role in the growth of microalgae and their nutrient composition. To elucidate the effect of different LED lights (red, orange, green, blue, purple, simulated sunlight, and white) on the main nutritional compositions of Isochrysis zhanjiangensis, the growth, fatty acid composition, soluble carbohydrate, and soluble protein contents were studied. The results show that I. zhanjiangensis grew the fastest under blue light (p = 0.044). In terms of fatty acid composition, the percentage of myristic acid (C14:0) decreased significantly (p = 0.021) under blue light and simulated sunlight, but the percentages of palmitic acid (C16:0) (p = 0.032) and stearic acid (C18:0) (p = 0.037) significantly increased. The percentage of docosahexaenoic acid (C22:6n-3) increased under orange light (p = 0.021), and the percentage of total unsaturated fatty acids increased under blue light (p = 0.008). The protein content significantly increased under simulated sunlight (p = 0.025), while the carbohydrate content did not vary much (p > 0.05) under different lights. These findings provide useful guidance for optimizing the cultivation conditions of I. zhanjiangensis to improve its nutritional value and yield.